2014
DOI: 10.1063/1.4897461
|View full text |Cite
|
Sign up to set email alerts
|

Edge effects on the electronic properties of phosphorene nanoribbons

Abstract: Two dimensional few-layer black phosphorus crystal structures have recently fabricated and demonstrated great potential in applications of electronics. In this work, we employed first principles density functional theory calculations to study the edge effects and quantum confinement on the electronic properties of the phosphorene nanoribbons (PNR). Different edge functionalization groups, such as H, F, Cl, OH, O, S, and Se in addition to a pristine case, were studied for a series width of the ribbon up to 3.5 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
154
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(171 citation statements)
references
References 37 publications
17
154
0
Order By: Relevance
“…13 lattice vectors, we realized that ZPNRs meet the Peierls instability(PI), which has been confirmed by Du et al, 14 where they reported the instability brought about susceptibility divergence. There are two universal mechanisms to remove the PI, namely charge density waves (CDW) 15 due to electron-phonon interaction and spin density waves(SDW) 16,17 due to electron-electron interaction.…”
Section: Nanoribbons (Zvnrs)supporting
confidence: 62%
See 1 more Smart Citation
“…13 lattice vectors, we realized that ZPNRs meet the Peierls instability(PI), which has been confirmed by Du et al, 14 where they reported the instability brought about susceptibility divergence. There are two universal mechanisms to remove the PI, namely charge density waves (CDW) 15 due to electron-phonon interaction and spin density waves(SDW) 16,17 due to electron-electron interaction.…”
Section: Nanoribbons (Zvnrs)supporting
confidence: 62%
“…In reality, hydrogen and halogen elements terminated ZPNRs have been studied theoretically, showing that the full saturated ZPNRs are good insulators. 13 In order to study the stability and properties of SDW, we exam 1/4 and 1/2 H-saturated nanoribbons by 1 × 4 × 1 supercell. The results still show the existence of magnetic moment at unsaturated edge seen in Fig.…”
Section: 52k B T S Dwmentioning
confidence: 99%
“…Previous theoretical 38 and experimental 39 works have demonstrated interesting features coming from the relaxation and passivation of edge structures in graphene nanoribbons, which provide additional ways of modifying their electronic structure. Analogously, it has been recent reported via first-principles calculations of BPNs passivated by H atoms 23 and functionalized by different edge groups 35 , such as H, F, Cl, OH, O, S, and Se, to stabilize the structures removing the edge dangling bonds. For instance, a considered case of zzBPN discussed in the present paper is sketched in Fig.…”
Section: Zigzag Phosphorene Nanoribbonsmentioning
confidence: 99%
“…Following the example of graphene nanoribbons [29][30][31] , one can expect that the electronic spectrum and the transport properties of narrow phosphorene ribbons can be significantly distinct from the case of an infinite sample. Recent studies of BPNs have been based on a tight-binding approach [32][33][34] and via first-principles simulations 23,24,35 that, while giving reasonably precise results for small structures, can become computationally expensive for larger structures. In addition, pure computational approaches are not appropriate to give physical insights into the basic mechanisms behind the results, which is of fundamental importance for a pure theoretical understanding.…”
Section: Introductionmentioning
confidence: 99%
“…Further, due to the weak interaction between second and third nearest neighbors, it can easily be deformed under uniaxial compression, becoming, in sequence, an indirect gap semiconductor, a semimetal, a metal, and ultimately undergoing a transition to a square lattice. [1,2,9] Phosphorene can, in principle, be cut and tailored into derived nanostructures [10][11][12]. An interesting feature of finite systems is the possibility of edge states.…”
mentioning
confidence: 99%